HP product variety management - Allon, Gad; Van Mieghem, Jan A.; Kolesov, Ilya ([London] : SAGE, 2016)
HP sells configure-to-order products. With millions of part combinations going into an order, the challenge is deciding which parts to keep in the portfolio to balance costs with revenues. The case explains how one would approach this problem before product introduction, but focuses on managing the existing portfolio.
Originally Published in: Allon, G., Van Mieghem, J., & Kolesov, I. (2010). HP Product Variety Management (case revised 14/03/2011). 5-310-511. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Product management -- Case studies; High technology industries -- Management -- Case studies; Computer industry -- Management -- Case studies